Nutritional strategies for football: Counteracting heat, cold, high altitude, and jet lag - Armstrong, L. E. (Journal of Sports Sciences, 2006)
Environmental factors often influence the physical and mental performance of football players. Heat, cold, high altitude, and travel across time zones (i.e. leading to jet lag) act as stressors that alter normal physiological function, homeostasis, metabolism, and whole-body nutrient balance. Rather than accepting performance decrements as inevitable, well-informed coaches and players should plan strategies for training and competition that offset environmental challenges. Considering the strength of scientific evidence, this paper reviews recommendations regarding nutritional interventions that purportedly counterbalance dehydration, hyperthermia, hypothermia, hypoxia, acute or chronic substrate deficiencies, sleep loss, and desynchronization of internal biological clocks.